Fuel cell cathode catalyst and preparation method thereof
By using Pt/Sb-SnO2 material in the fuel cell cathode catalyst and using doped antimony Sb ions and atomic layer deposition processes, the problem of poor stability of commercial carbon-supported platinum catalysts in harsh environments is solved, and the support stability and conductivity is improved, the catalyst life is extended and the Oswald maturation process is slowed down.
Patent Information
- Application Number
- CN202510055297.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-15
AI Technical Summary
Commercial carbon-loaded platinum catalysts have problems such as poor stability, accelerated oxidation and corrosion, accelerated Oswald maturation process, and shedding and aggregation of platinum nanoparticles in the harsh environment of fuel cells, resulting in a decrease in catalyst efficiency and shortened lifetime.
Pt/Sb-SnO2 is used as the cathode catalyst of the fuel cell. The catalyst is prepared in the fluidized bed by doping antimony Sb ions in the tin dioxide SnO2 support and using the atomic layer deposition process to improve the stability and conductivity of the support and alleviate the Oswald maturation process.
It improves the stability and conductivity of the catalyst support, extends the service life of the catalyst, slows down the Oswald maturation process, and maintains efficient catalytic activity and stability.
Smart Images

Figure CN119833660A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, in particular to a fuel cell cathode catalyst. The present invention also provides a method for preparing the fuel cell cathode catalyst. Background Art
[0002] Fuel cells have the advantages of high efficiency, environmental protection, and quiet operation. They directly convert chemical energy into electrical energy through electrochemical reactions, with high efficiency and almost no pollutant emissions. Among them, proton exchange membrane fuel cells (PEMFC) are widely used in transportation, portable devices, and fixed power sources due to their fast start-up, high power density, and low operating temperature. As the core component of PEMFC, the membrane electrode (MEA) determines the performance and life of the battery, and the most critical part of the membrane electrode is the catalyst coated membrane (CCM), which directly affects the efficiency and stability of the electrochemical reaction.
[0003] Platinum (Pt) has excellent electrocatalytic activity and can efficiently catalyze the oxygen reduction reaction and hydrogen oxidation reaction in fuel cells. These two reactions are the key steps for fuel cells to generate electricity. At the same time, Pt, as a catalyst, can selectively promote the required electrochemical reactions and reduce unnecessary side reactions, thereby improving the energy conversion efficiency and stability of fuel cells. Pt is a rare and expensive metal. In order to reduce the amount of Pt used while maintaining the catalytic performance of Pt, commercial carbon-supported platinum (Pt / C) catalysts are usually used to prepare CCM. The active component (Pt nanoparticles) is adsorbed on the carbon carrier (C) through physical action. The particle size of Pt nanoparticles is usually designed to be 2-5nm. Compared with the early platinum black catalyst of fuel cells, Pt / C catalysts reduce the amount of Pt used by an order of magnitude while maintaining the catalytic ability equivalent to that of platinum black. Secondly, due to the limitation of the carbon carrier, the agglomeration effect of Pt nanoparticles (compared with platinum black) is suppressed, which is beneficial to prolonging the service life of the Pt / C catalyst. In addition, the carbon-based carrier of the Pt / C catalyst is a material with high electrical conductivity, which is conducive to the transmission of electrons.
[0004] However, commercial carbon-supported platinum catalysts have the following disadvantages as cathode catalysts for PEMFC:
[0005] First, the stability of the carbon carrier is poor. In the harsh operating environment of the fuel cell, the carbon carrier faces severe chemical corrosion and potential corrosion. In the cathode of the fuel cell, the catalyst will be exposed to high temperature and strong oxidizing working environment for a long time. The oxidizing intermediate species of the cathode will promote the corrosion of carbon, weaken the porous structure of the carbon carrier, and cause the Pt nanoparticles to fall off and agglomerate, making the catalyst gradually ineffective.
[0006] Secondly, after the fuel cell is shut down and hydrogen is cut off, the oxygen in the air will gradually pass through the proton exchange membrane to the anode side. After a long period of static, restarting the fuel cell will form a hydrogen-air interface at the anode of one or several membrane electrodes. There will be both hydrogen-rich and oxygen-rich areas at the anode. This is the phenomenon of lack of gas in the anode part of the membrane electrode. The hydrogen-rich area will form a normal forward current, which will charge the oxygen-rich area and form a "galvanic cell-electrolytic cell" structure inside the membrane electrode. At this time, the oxygen-rich area will generate an abnormal reverse current, and the cathode potential will increase abnormally. The high potential will promote carbon corrosion, weaken the porous structure of the carbon carrier, and cause the Pt nanoparticles to fall off and agglomerate, further causing a reduction in the electrochemical active area of the catalyst. The detached platinum nanoparticles will be electrically isolated and unable to play a catalytic role.
[0007] Second, commercial carbon-supported platinum catalysts usually have a particle size range of 2.8nm-4.5nm, and their size distribution is wide, which is not conducive to alleviating the Oswald ripening process; the surface energy of platinum nanoparticles is related to their particle size, with smaller nanoparticles having higher surface energy and larger particles having lower surface energy; platinum nanoparticles tend to reduce their surface energy during the catalytic process to reduce free energy; when the size difference of platinum nanoparticles is large, their surface energy difference is large, which will accelerate the Oswald ripening process;
[0008] Third, for commercial carbon-supported platinum catalysts, the position distribution of platinum nanoparticles is relatively uneven, which will cause the attraction between some nanoparticles to be too strong, and smaller nanoparticles will merge into larger particles, which will also accelerate the Oswald ripening process;
[0009] Fourth, in commercial carbon-supported platinum (Pt / C) catalysts, the active component Pt nanoparticles are supported on the C carrier by physical adsorption, which has limited effect and is not conducive to alleviating the migration of Pt nanoparticles, and thus it is difficult to alleviate the Oswald ripening process. Summary of the invention
[0010] In view of the above problems, the present invention provides a fuel cell cathode catalyst, which makes the carrier stable and helps to alleviate the Oswald ripening process.
[0011] A fuel cell cathode catalyst, characterized in that its material is Pt / Sb-SnO2.
[0012] Its further characteristic is that it uses tin dioxide SnO2 as a carrier, dopes antimony Sb ions into the carrier to obtain Sb-SnO2, and then uses atomic layer deposition process in a fluidized bed to prepare Pt / Sb-SnO2 catalyst.
[0013] It is further characterized in that: the doping ratio of antimony Sb ions doped in the carrier is 5 mol%;
[0014] Pt / Sb-SnO2 was used as the catalyst, wherein the Pt content was 20%.
[0015] Tin dioxide SnO2 is used as a carrier of the cathode catalyst of the fuel cell; firstly, SnO2 has high thermal stability (melting point can reach 1630°C), and within the operating temperature range of the PEMFC, SnO2 can maintain good structural stability; secondly, in an air atmosphere, SnO2 exhibits good resistance to oxidative corrosion, which is due to the fact that tin has a stable +4 oxidation state, which is relatively stable and not easily further oxidized; thirdly, within the operating potential range of the fuel cell, SnO2 exhibits good potential corrosion resistance, and the +4 oxidation state of tin remains relatively stable; in the absence of doping, the outermost electrons of all atoms in the SnO2 crystal are used to form the valence band, and the electrons in the valence band are bound in the chemical bonds between atoms and cannot move freely; the conduction band is empty, and no electrons can move freely to conduct current; there is a band gap between the valence band and the conduction band, and since the band gap of SnO2 is relatively wide (E=3.6eV), a considerable amount of energy is required to excite from the highest energy level of the valence band to the lowest energy level of the conduction band, so the conductivity of SnO2 is relatively poor;
[0016] In order to significantly improve the conductivity of SnO2 materials, the present invention doped antimony Sb ions into SnO2 materials, namely antimony doped tin oxide (ATO); Sb ions were used to replace Sn ions in normal positions in the SnO2 lattice, artificially causing a mismatch in the SnO2 stoichiometric number, thereby generating excess electrons, which were bound around the Sb ions, and this binding was very weak. At room temperature, they could break away from the Sb ions and move freely in the crystal to form n-type carriers; Sb 5+ A shallow donor energy level is formed in the band gap of SnO2 and provides electrons to the conduction band, greatly improving the conductivity of antimony-doped tin dioxide;
[0017] The doping ratio of antimony ions in the present invention is 5 mol%, because as the doping concentration of antimony ions changes, the two oxidation states of antimony ions (Sb 5+ and Sb 3+ ) there is competition; when Sb 5+ Replace Sn 4+ When Sb 5+ Sn 4+ An extra positive charge will leave an extra hole, generating a shallow donor energy level very close to the bottom of the conduction band. The shallow donor energy level can easily release electrons to the conduction band, thereby increasing the number of free electrons in the conduction band, which is beneficial to the improvement of the conductivity of antimony-doped tin dioxide. 3+ Replace Sn4+ When Sb 3+ Sn 4+ One less positive charge will leave an extra electron, resulting in a shallow acceptor energy level very close to the top of the valence band. The shallow acceptor energy level can easily capture electrons from the valence band, thereby reducing the number of free electrons in the conduction band, which is not conducive to the improvement of the conductivity of antimony-doped tin dioxide. 5+ and Sb 3+ When the antimony doping level is low, the antimony is mainly in the form of Sb 5+ Entering the SnO2 lattice to replace Sn 4+ ; As the antimony doping ratio increases, part of the antimony begins to be Sb 3+ into the SnO2 lattice replacing Sn 4+ Therefore, the preferred antimony doping ratio of the present invention is 5 mol%; since the working atmosphere of the cathode of the fuel cell is an oxidizing atmosphere and the conductive mechanism of antimony-doped tin dioxide is mainly composed of Sb 5+ Therefore, in the working environment of the fuel cell cathode, antimony-doped tin dioxide can maintain a relatively high conductivity.
[0018] A method for preparing a fuel cell cathode catalyst, characterized in that it comprises the following steps:
[0019] S1, using tin dioxide SnO2 as a carrier of the fuel cell cathode catalyst;
[0020] S2, preparing cathode catalyst carrier antimony-doped tin dioxide by dry gel method;
[0021] S3. Prepare Pt / Sb-SnO2 catalyst in a fluidized bed using atomic layer deposition process.
[0022] It is further characterized by:
[0023] In step S2, anhydrous ethanol is added to a clean beaker, magnetic stirring is turned on, and the PTFE rotor rotates; anhydrous tin tetrachloride liquid is dissolved in anhydrous ethanol; then pure antimony trichloride is dissolved in anhydrous ethanol; deionized water is then added to the anhydrous ethanol, and stirring is continued for 15 minutes under a nitrogen atmosphere; finally, high-grade pure propylene oxide is added dropwise, and stirring is continued to obtain an alcohol gel of Sb-SnO2; the gel is aged at room temperature to obtain an aged gel; thereafter, the aged gel is solvent-exchanged once with an acetone solvent at set intervals, and the solvent exchange is performed continuously for multiple times to obtain a dry gel; the dry gel is annealed in an air atmosphere to obtain an antimony-doped tin dioxide powder, which is recorded as Sb-SnO2;
[0024] In step S3, the synthesis of the catalyst is completed in a vibrating fluidized bed reactor, Sb-SnO2 is added to a columnar reactor, and dried at 300°C to remove water adsorbed by Sb-SnO2; trimethyl platinum is used as a platinum precursor, and since solid trimethyl platinum at room temperature hardly evaporates, it is placed in a bubbler at 70°C to form trimethyl platinum vapor; multiple cycles of deposition treatment are performed to prepare a Pt / Sb-SnO2 (5 mol%) catalyst with a platinum content of 20%;
[0025] Each deposition cycle includes the following steps: using nitrogen as a carrier gas to transport trimethyl platinum vapor from a bubbler at 70°C to a column reactor at 300°C, with a superficial gas flow rate of 0.3 cm / s for nitrogen and a dosage time of 7 min for platinum precursor; purging with nitrogen for 5 min at a superficial gas flow rate of 0.3 cm / s; then evacuating the reaction system; introducing oxygen into the column reactor at 300°C at a superficial gas flow rate of 0.3 cm / s for an oxygen dosage time of 20 min to oxidize the organic portion of the platinum precursor; purging with nitrogen for 5 min at a superficial gas flow rate of 0.3 cm / s to remove unreacted precursors and other products; then evacuating the reaction system;
[0026] Since the conductive mechanism of the carrier material Sb-SnO2 is mainly composed of Sb 5+ Therefore, the Sb-SnO2 carrier material is suitable for working in an oxidizing atmosphere to maintain a high conductivity, so Sb-SnO2 is suitable as a carrier of a fuel cell cathode catalyst.
[0027] It is further characterized by:
[0028] Step S2 obtains 5 mol% antimony-doped tin dioxide powder, recorded as Sb-SnO2 (5 mol%);
[0029] Step S3 obtains a Pt / Sb-SnO2 (5 mol%) catalyst having a platinum content of 20%.
[0030] After adopting the present invention, the carrier stability of the Pt / Sb-SnO2 catalyst is good and it is beneficial to alleviate the Oswald ripening process. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a size distribution diagram of the invented platinum nanoparticles;
[0032] Figure 2 is a position distribution diagram of platinum nanoparticles of the present invention;
[0033] Figure 3 The load cycle results of RDE1 and RDE2 are Figure 1 ;
[0034] Figure 4 The load cycle results of RDE1 and RDE2 are Figure 2 ;
[0035] Figure 5 To start and stop the RDE3 and RDE4 Figure 1 ;
[0036] Figure 6 To start and stop the RDE3 and RDE4 Figure 2 . DETAILED DESCRIPTION
[0037] A fuel cell cathode catalyst: its material is Pt / Sb-SnO2.
[0038] In a preferred embodiment, tin dioxide SnO2 is used as a carrier, antimony Sb ions are doped into the carrier to obtain Sb-SnO2, and the doping ratio of antimony Sb ions in the carrier is 5 mol%; then an atomic layer deposition process is used in a fluidized bed to prepare a Pt / Sb-SnO2 (5 mol%) catalyst, in which the Pt content is 20%.
[0039] Tin dioxide SnO2 is used as a carrier of the cathode catalyst of the fuel cell; firstly, SnO2 has high thermal stability (melting point can reach 1630°C), and within the operating temperature range of the PEMFC, SnO2 can maintain good structural stability; secondly, in an air atmosphere, SnO2 exhibits good resistance to oxidative corrosion, which is due to the fact that tin has a stable +4 oxidation state, which is relatively stable and not easily further oxidized; thirdly, within the operating potential range of the fuel cell, SnO2 exhibits good potential corrosion resistance, and the +4 oxidation state of tin remains relatively stable; in the absence of doping, the outermost electrons of all atoms in the SnO2 crystal are used to form the valence band, and the electrons in the valence band are bound in the chemical bonds between atoms and cannot move freely; the conduction band is empty, and no electrons can move freely to conduct current; there is a band gap between the valence band and the conduction band, and since the band gap of SnO2 is relatively wide (E=3.6eV), a considerable amount of energy is required to excite from the highest energy level of the valence band to the lowest energy level of the conduction band, so the conductivity of SnO2 is relatively poor;
[0040] In order to significantly improve the conductivity of SnO2 materials, the present invention doped antimony Sb ions into SnO2 materials, namely antimony doped tin oxide (ATO); Sb ions were used to replace Sn ions in normal positions in the SnO2 lattice, artificially causing a mismatch in the SnO2 stoichiometric number, thereby generating excess electrons, which were bound around the Sb ions, and this binding was very weak. At room temperature, they could break away from the Sb ions and move freely in the crystal to form n-type carriers; Sb 5+ A shallow donor energy level is formed in the band gap of SnO2 and provides electrons to the conduction band, greatly improving the conductivity of antimony-doped tin dioxide;
[0041] The doping ratio of antimony ions in the present invention is 5 mol%, because as the doping concentration of antimony ions changes, the two oxidation states of antimony ions (Sb 5+ and Sb 3+ ) there is competition; when Sb 5+ Replace Sn 4+ When Sb 5+ Sn 4+ An extra positive charge will leave an extra hole, generating a shallow donor energy level very close to the bottom of the conduction band. The shallow donor energy level can easily release electrons to the conduction band, thereby increasing the number of free electrons in the conduction band, which is beneficial to the improvement of the conductivity of antimony-doped tin dioxide. 3+ Replace Sn 4+ When Sb 3+ Sn 4+ One less positive charge will leave an extra electron, resulting in a shallow acceptor energy level very close to the top of the valence band. The shallow acceptor energy level can easily capture electrons from the valence band, thereby reducing the number of free electrons in the conduction band, which is not conducive to the improvement of the conductivity of antimony-doped tin dioxide. 5+ and Sb 3+ When the antimony doping level is low, the antimony is mainly in the form of Sb 5+ Entering the SnO2 lattice to replace Sn 4+ ; As the antimony doping ratio increases, part of the antimony begins to be Sb 3+ into the SnO2 lattice replacing Sn 4+ Therefore, the preferred antimony doping ratio of the present invention is 5 mol%; since the working atmosphere of the cathode of the fuel cell is an oxidizing atmosphere and the conductive mechanism of antimony-doped tin dioxide is mainly composed of Sb 5+ Therefore, in the working environment of the fuel cell cathode, antimony-doped tin dioxide can maintain a relatively high conductivity.
[0042] A method for preparing a fuel cell cathode catalyst, wherein the fuel cell cathode catalyst is a Pt / Sb-SnO2 (5 mol%) catalyst, wherein the Pt content is 20%, comprising the following steps:
[0043] S1, using tin dioxide SnO2 as a carrier of the fuel cell cathode catalyst;
[0044] S2, preparing cathode catalyst carrier antimony-doped tin dioxide by dry gel method;
[0045] Add 200 ml of anhydrous ethanol to a clean beaker, turn on magnetic stirring, and set the speed of the PTFE rotor to 100 RPM; first take 17.81 g of anhydrous tin tetrachloride liquid and dissolve it in 200 ml of anhydrous ethanol; then take 0.82 g of high-grade pure antimony trichloride and dissolve it in the above 200 ml of anhydrous ethanol; then add 3 ml of deionized water to the anhydrous ethanol and continue stirring under nitrogen atmosphere for 15 minutes; finally, add 12 ml of high-grade pure propylene oxide dropwise at 100 RPM. After stirring at a stirring rate of 1.50 M for 10 min, an alcohol gel of Sb-SnO2 was obtained; the gel was aged at room temperature for 24 h to obtain an aged gel; thereafter, the aged gel was solvent exchanged with acetone solvent once every 24 h, and the solvent exchange was performed 7 times in succession to obtain a dry gel; the dry gel was annealed in an air atmosphere at an annealing temperature of 600°C for 1.5 h to obtain 5 mol% antimony-doped tin dioxide powder, recorded as Sb-SnO2 (5 mol%);
[0046] S3, using an atomic layer deposition process in a fluidized bed to prepare a Pt / Sb-SnO2 (5 mol%) catalyst, wherein the Pt content is 20%;
[0047] The fluidized bed consists of a column reactor, a vibration generation system, a data acquisition system, a control system, and an in-situ mass spectrometer;
[0048] The synthesis of the catalyst is completed in a vibrating fluidized bed reactor to improve the quality of particle fluidization; 10 g of Sb-SnO2 (5 mol%) is added to a column reactor and dried at 300°C for 5 hours to remove the water adsorbed by Sb-SnO2 (5 mol%); trimethyl (methylcyclopentadienyl) platinum is used as a platinum precursor. Since solid trimethyl (methylcyclopentadienyl) platinum at room temperature hardly evaporates, it is placed in a bubbler at 70°C to form trimethyl (methylcyclopentadienyl) platinum vapor; a deposition cycle includes the following steps: nitrogen is used as a carrier gas to transport trimethyl (methylcyclopentadienyl) platinum vapor from the bubbler at 70°C to the column reactor at 300°C, and the apparent gas flow of nitrogen is 1:1. The speed was 0.3 cm / s, and the dosage time of the platinum precursor was 7 minutes; nitrogen was purged for 5 minutes, and the apparent gas flow rate was 0.3 cm / s; the reaction system was evacuated; oxygen was introduced into the columnar reactor at 300°C, the apparent gas flow rate of oxygen was 0.3 cm / s, and the dosage time of oxygen was 20 minutes to oxidize the organic part of the platinum precursor; nitrogen was purged for 5 minutes, and the apparent gas flow rate was 0.3 cm / s to remove the unreacted precursor and other products; the reaction system was evacuated again; the platinum content was affected by the deposition time of the reactor; Pt / Sb-SnO2 (5 mol%) was deposited for a total of 6 cycles to prepare a Pt / Sb-SnO2 (5 mol%) catalyst with a platinum content of 20%.
[0049] Since the conductive mechanism of the support material Sb-SnO2 (5 mol%) is mainly composed of Sb 5+ Therefore, the Sb-SnO2 (5 mol%) carrier material is suitable for working in an oxidizing atmosphere to maintain high conductivity, so Sb-SnO2 (5 mol%) is suitable as a carrier of the cathode catalyst of the fuel cell.
[0050] After repeated tests, it was found that 600℃ is the best annealing temperature; when the annealing temperature is between 300℃ and 500℃, the oxidation degree of antimony ions is insufficient, and Sb 5+ The content of Sb-SnO2 (5mol%) is relatively small, and the conductivity of Sb-SnO2 (5mol%) does not increase significantly, and its conductivity is only 0.6S / cm; when the annealing temperature continues to increase to 600°C, the conductivity of Sb-SnO2 (5mol%) significantly increases to 6.2S / cm; when the annealing temperature continues to increase on the basis of 600°C, the specific surface area of Sb-SnO2 (5mol%) will be significantly reduced; therefore, the annealing conditions (600°C and 1.5h) selected in the present invention take into account both the conductivity and specific surface area of Sb-SnO2 (5mol%).
[0051] The advantages of using a fluidized bed to synthesize catalysts are: each solid particle forms a flow state under the push of the gas, and the solid particles can freely tumble up and down and diffuse horizontally, showing a high degree of dynamic mixing; because the solid particles are in a state of continuous motion in the fluidized bed, the contact area with the fluid or other solid particles is greatly increased, which greatly promotes the material transfer and heat exchange between solids and between gases and solids, and is conducive to fast and efficient physical processes and chemical reactions.
[0052] The element distribution diagrams of transmission electron microscopy and energy dispersive X-ray spectroscopy are used to characterize the size distribution and position distribution of platinum deposited on the Sb-SnO2 (5 mol%) cathode carrier by the atomic layer deposition method used in the present invention; the size distribution diagram of platinum nanoparticles is shown in FIG. Figure 1 As shown in the figure, 49.7% of the platinum nanoparticles are about 3nm in size; 2-4nm platinum particles account for 88.3%, and the size distribution is relatively narrow. This is because the platinum precursor trimethyl (methylcyclopentadienyl) platinum has a self-limiting reaction mechanism; the Oswald ripening mechanism refers to the process in which smaller particles merge or grow to form larger particles; since the surface area of the platinum nanoparticles will decrease, this will lead to a decrease in the catalytic activity of platinum; when the size distribution of platinum nanoparticles is narrow, the chemical potential between the platinum nanoparticles is closer, and the Oswald ripening rate is slowed down, thereby improving the stability of the catalyst and the long-term catalytic effect; the position distribution of platinum nanoparticles is shown in the figure Figure 2 The red color is platinum and the green color is tin. It can be seen that the platinum nanoparticles are evenly dispersed on the Sb-SnO2 (5 mol%) carrier. When the dispersion is relatively uniform, each platinum particle can be fixed in a relatively stable position, avoiding the strong attraction between particles that causes the small particles to merge with each other, thus slowing down the process of Oswald ripening.
[0053] The present invention adopts atomic layer deposition method, uses trimethyl (methylcyclopentadienyl) platinum as a noble metal precursor, and introduces oxygen to react at 300°C; the advantage of this preparation method is that no reducing agent is directly introduced, avoiding the reduction of Sb in the carrier material Sb-SnO2 (5mol%). 5+ After the conductivity characterization, the conductivity of the Pt / Sb-SnO2 catalyst was 7.6S / cm, which exceeded the 6.2S / cm of the Sb-SnO2 carrier material, which shows that the atomic layer deposition method used in the present invention will not affect the Sb in the carrier material. 5+ Cause interference, and because Sb-SnO2 is loaded with Pt, its overall conductivity is enhanced.
[0054] The Pt / Sb-SnO2 (5 mol%) catalyst prepared by the present invention and the commercial Pt / C catalyst were characterized for the hydrogen zone active area using an electrochemical workstation, and the platinum content of both catalysts was 20%;
[0055] The test conditions for characterizing the hydrogen zone active area are as follows:
[0056] Ⅰ: The electrochemical test system is "0.5M H2SO4 solution saturated with nitrogen, the test environment temperature is 25℃, the scan rate is 50mV / s, the potential scan range is 0.08V-1.2V (vs.RHE), and the number of scan segments is 4; where RHE represents reversible hydrogen electrode;
[0057] Ⅱ: Glassy carbon electrode is used as the working electrode. The geometric area of the working electrode is 0.19625cm 2 ; The graphite electrode is used as the auxiliary electrode, and the contact area between the graphite and the solution system is ≥10cm 2 ; Saturated calomel electrode was used as reference electrode;
[0058] III: The electrochemical test ink is composed of a dispersant and a dispersant, wherein the dispersant is a catalyst, and the dispersant is ultrapure water, ethanol and Nafion resin emulsion; wherein the Nafion resin emulsion contains 5% dry resin and 95% solvent, the volume of the dry resin is negligible and the entire Nafion resin emulsion is regarded as part of the dispersant; the ratio of the dispersant is: 1ml dispersant = 0.5ml ultrapure water + 0.5ml ethanol + 0.05ml Nafion resin emulsion; the catalyst solid content of the electrochemical test ink is 1mg (catalyst) / ml (dispersant); the ink volume is accurately measured by a pipette and titrated on the working electrode to ensure that the catalyst loading on the working electrode is 20mg / cm 2 ;
[0059] The characterization results of the hydrogen zone active area of the Pt / Sb-SnO2 (5 mol%) catalyst and the commercial Pt / C catalyst are listed in Table 1.
[0060]
[0061] Table 1
[0062] It can be seen from Table 1 that the hydrogen zone active area of the Pt / Sb-SnO2 (5 mol%) catalyst is very close to that of the commercial Pt / C catalyst;
[0063] The catalytic activity of the Pt / Sb-SnO2 (5 mol%) catalyst prepared by the present invention and the commercial Pt / C catalyst for oxygen reduction reaction was characterized using an electrochemical workstation and a rotating disk electrode system. The platinum content of both catalysts was 20%.
[0064] The test conditions for the catalytic activity (specific mass activity) of the oxygen reduction reaction are as follows:
[0065] Ⅰ: The electrochemical test system is an oxygen-saturated 0.1M HClO4 solution, and oxygen needs to be continuously introduced during the test; the test environment temperature is 25°C, the scan rate is 10mV / s, the potential scan range is 0.1-1.1V (vs.RHE), and the rotation speed of the rotating disk electrode system is 1600RPM;
[0066] Ⅱ: Glassy carbon electrode as working electrode, the geometric area of the working electrode is 0.19625cm 2 ; The graphite electrode is used as the auxiliary electrode, and the contact area between the graphite and the solution system is ≥10cm 2 ; RHE is used as the reference electrode, and the electrolyte of RHE is 0.1M HClO4, which is exactly the same as the electrolyte of the electrolytic cell;
[0067] III: The electrochemical test ink is composed of a dispersant and a dispersant, wherein the dispersant is a catalyst, and the dispersant is ultrapure water, ethanol and Nafion resin emulsion; wherein the Nafion resin emulsion contains 5% dry resin and 95% solvent, the volume of the dry resin is negligible and the entire Nafion resin emulsion is regarded as part of the dispersant; the ratio of the dispersant is: 1ml dispersant = 0.5ml ultrapure water + 0.5ml ethanol + 0.05ml Nafion resin emulsion; the catalyst solid content of the electrochemical test ink is 1mg (dispersant) / ml (dispersant); the ink volume is accurately measured by a pipette and titrated on the working electrode to ensure that the platinum content of the catalyst on the working electrode is 20mg / cm 2 ;
[0068] The specific mass activity characterization results of Pt / Sb-SnO2 (5 mol%) catalyst and commercial Pt / C catalyst are listed in Table 2
[0069]
[0070] Table 2
[0071] It can be seen from Table 2 that the specific mass activity of the Pt / Sb-SnO2 (5 mol%) catalyst is very close to that of the commercial Pt / C catalyst;
[0072] In order to evaluate the durability of the active components and the carrier of the Pt / Sb-SnO2 catalyst, a load cycle durability test and a start-stop cycle durability test were carried out on a rotating disk electrode (RDE) to evaluate the degradation of the precious metal nanoparticles and the catalyst carrier, respectively; the potential scanning range of the load cycle durability test was 0.6V-0.95V, using a square wave cycle, holding at 0.6V for 3s, holding at 0.95s for 3s, the potential switching time was <0.5s, each cycle lasted for 6s, and 10,000 cycles were performed; the potential scanning range of the start-stop cycle durability test was 1V-1.5V, using a triangle wave cycle, the scanning rate was 0.5V / s, each cycle was 2s, and 10,000 cycles were performed;
[0073] Two samples, RDE1 and RDE2, were prepared using commercial Pt / C catalyst and Pt / Sb-SnO2 (5 mol%) catalyst respectively to characterize the hydrogen zone active area after load cycle; two samples, RDE3 and RDE4, were prepared using commercial Pt / C catalyst and Pt / Sb-SnO2 (5 mol%) catalyst respectively to characterize the hydrogen zone active area after start-stop cycle;
[0074] The load cycle results of RDE1 and RDE2 are listed in Figure 3 , Figure 4 and Table 3;
[0075] sample <![CDATA[Starting hydrogen area (m 2 / g)]]> <![CDATA[End hydrogen zone area (m 2 / g)]]> Loss Rate RDE1 83 45.65 45% RDE2 74 57.72 22%
[0076] Table 3
[0077] from Figure 3 , Figure 4 As can be seen from Table 3, after 10,000 load cycles, the hydrogen zone area loss of the Pt / Sb-SnO2 (5 mol%) catalyst is only 22%, which is better than the commercial Pt / C catalyst; firstly, in the Pt / Sb-SnO2 (5 mol%) catalyst, the uniformity of the size of the platinum nanoparticles almost makes the chemical potential of different platinum nanoparticles equal, which alleviates the Oswald ripening process; secondly, the uniformity of the position of the platinum nanoparticles further alleviates the Oswald ripening process; thirdly, the strong interaction between the metal (Pt) and the carrier (Sb-SnO2) can alleviate the dissolution of platinum to improve the stability of the Pt / Sb-SnO2 (5 mol%) catalyst;
[0078] The results after the start-stop cycle of RDE3 and RDE4 are listed in Figure 5 , Figure 6 and Table 4;
[0079]
[0080]
[0081] Table 4
[0082] from Figure 5 , Figure 6 As can be seen from Table 4, after 10,000 start-stop cycles, the hydrogen zone area loss of the commercial Pt / C catalyst is as high as 57.6%, while the hydrogen zone area of the Pt / Sb-SnO2 (5 mol%) catalyst is almost not lost, which shows the superior stability of the carrier material Sb-SnO2; the attenuation of the electrochemical active area of the commercial Pt / C catalyst is better than the dissolution and isolation of the platinum nanoparticles caused by the electrochemical corrosion of carbon; so the Pt / Sb-SnO2 (5 mol%) catalyst prepared by the present invention is close to the commercial Pt / C catalyst in terms of hydrogen zone active area and specific mass activity, but in terms of 10,000 load cycles and 10,000 start-stop cycles, the Pt / Sb-SnO2 (5 mol%) catalyst is superior to the commercial Pt / C catalyst.
[0083] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0084] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A fuel cell cathode catalyst, characterized in that: Its material is Pt / Sb-SnO2.
2. A fuel cell cathode catalyst according to claim 1, characterized in that: It uses tin dioxide SnO2 as a carrier, dopes antimony Sb ions into the carrier to obtain Sb-SnO2, and then uses atomic layer deposition process in a fluidized bed to prepare Pt / Sb-SnO2 catalyst.
3. A fuel cell cathode catalyst according to claim 2, characterized in that: The doping ratio of antimony (Sb) ions doped in the carrier is 5 mol%.
4. A fuel cell cathode catalyst according to claim 3, characterized in that: The Pt content is 20%.
5. A method for preparing a fuel cell cathode catalyst, which is used to prepare the fuel cell cathode catalyst according to any one of claims 1 to 4, characterized in that: It includes the following steps: S1, using tin dioxide SnO2 as a carrier of the fuel cell cathode catalyst; S2, preparing cathode catalyst carrier antimony-doped tin dioxide by dry gel method; S3. Prepare Pt / Sb-SnO2 catalyst in a fluidized bed using atomic layer deposition process.
6. The method for preparing a fuel cell cathode catalyst according to claim 1, characterized in that: In step S2, anhydrous ethanol is added to a clean beaker, magnetic stirring is turned on, and the polyfluoro rotor rotates; anhydrous tin tetrachloride liquid is dissolved in anhydrous ethanol; then pure antimony trichloride is dissolved in anhydrous ethanol; deionized water is then added to the anhydrous ethanol, and stirring is continued for 15 minutes under a nitrogen atmosphere; finally, high-purity propylene oxide is added dropwise, and stirring is continued to obtain an alcohol gel of Sb-SnO2; the gel is aged at room temperature to obtain an aged gel; thereafter, the aged gel is solvent exchanged once with acetone solvent at set intervals, and the solvent exchange is performed continuously for multiple times to obtain a dry gel; the dry gel is annealed in an air atmosphere to obtain antimony-doped tin dioxide powder, which is recorded as Sb-SnO2.
7. The method for preparing a fuel cell cathode catalyst according to claim 5, characterized in that: In step S3, the synthesis of the catalyst is completed in a vibrating fluidized bed reactor, Sb-SnO2 is added to a columnar reactor, and dried at 300°C to remove water adsorbed by Sb-SnO2; trimethyl platinum is used as a platinum precursor, and since solid trimethyl platinum at room temperature hardly evaporates, it is placed in a bubbler at 70°C to form trimethyl platinum vapor; multiple cycles of deposition treatment are performed to prepare a Pt / Sb-SnO2 (5 mol%) catalyst with a platinum content of 20%; Each deposition cycle includes the following steps: using nitrogen as a carrier gas to transport trimethylplatinum vapor from a bubbler at 70°C to a column reactor at 300°C, with an apparent gas flow rate of 0.3 cm / s for nitrogen and a dosage time of 7 min for the platinum precursor; purging with nitrogen for 5 min at an apparent gas flow rate of 0.3 cm / s; evacuating the reaction system; introducing oxygen into the column reactor at 300°C at an apparent gas flow rate of 0.3 cm / s for an oxygen dosage time of 20 min to oxidize the organic portion of the platinum precursor; purging with nitrogen for 5 min at an apparent gas flow rate of 0.3 cm / s to remove unreacted precursors and other products; and evacuating the reaction system.
8. The method for preparing a fuel cell cathode catalyst according to claim 7, characterized in that: Since the conductive mechanism of the carrier material Sb-SnO2 is mainly composed of Sb 5+ Therefore, the Sb-SnO2 carrier material is suitable for working in an oxidizing atmosphere to maintain a high conductivity, so Sb-SnO2 is suitable as a carrier of a fuel cell cathode catalyst.
9. The method for preparing a fuel cell cathode catalyst according to claim 6, characterized in that: Step S2 obtains 5 mol % antimony-doped tin dioxide powder, which is recorded as Sb-SnO2 (5 mol %).
10. The method for preparing a fuel cell cathode catalyst according to claim 7, characterized in that: Step S3 obtains a Pt / Sb-SnO2 (5 mol%) catalyst having a platinum content of 20%.